Digital Me : Trans Students Exploring Future Possible Selves Online - Nicolazzo, Z.; Simms, Sy; Jones, Alden C. (Book collections on Project MUSE., 2023)
"The internet is where trans people have come to become. Creating an identity in digital space can be important for how trans people learn about themselves, their communities, and the possibilities available to them. While the internet and digital space is not the only way of coming to understand oneself in a community, it is a space of liberatory possibility and creativity. There is room to invent what may not yet exist for gender on the edges of what many consider to be "real." For many, digital life can be the site of play, joy, and connection -even while the internet is not a harm-free space nor universally available. This book seeks to understand the complexities at play in the digital realm and the implications that have for gender, digital life, and higher education"--